Diabetes Prevention and Care Capacity at Urban Indian Health Organizations - Fort, Meredith P.; Reid, Margaret; Russell, Jenn; Santos, Cornelia J.; Running Bear, Ursula; Begay, Rene L.; Smith, Savannah L.; Morrato, Elaine H.; Manson, Spero M. (Frontiers in Public Health, 2021)
American Indian and Alaska Native (AI/AN) people suffer a disproportionate burden of diabetes and cardiovascular disease. Urban Indian Health Organizations (UIHOs) are an important source of diabetes services for urban AI/AN people. Two evidence-based interventions – diabetes prevention (DP) and healthy heart (HH) – have been implemented and evaluated primarily in rural, reservation settings. This work examines the capacity, challenges and strengths of UIHOs in implementing diabetes programs. Methods: We applied an original survey, supplemented with publicly-available data, to assess eight organizational capacity domains, strengths and challenges of UIHOs with respect to diabetes prevention and care. We summarized and compared (Fisher’s and Kruskal-Wallis exact tests) items in each organizational capacity domain for DP and HH implementers versus non-implementers and conducted a thematic analysis of strengths and challenges. Results: Of the 33 UIHOs providing services in 2017, individuals from 30 sites (91% of UIHOs) replied to the survey. Eight UIHOs (27%) had participated in either DP (n=6) or HH (n=2). Implementers reported having more staff than non-implementers (117.0 vs 53.5; p=0.02). Implementers had larger budgets, approximately 10 million of total revenue compared to 2.5 million for non-implementers (p = 0.01). UIHO strengths included: physical infrastructure, dedicated leadership and staff, and community relationships. Areas to strengthen included: staff training and retention, ensuring sufficient and consistent funding, and data infrastructure. Conclusions: Strengthening UIHOs across organizational capacity domains will be important for implementing evidence-based diabetes interventions, increasing their uptake, and sustaining these interventions for AI/AN people living in urban areas of the U.S.